Kajian Historis Pendidikan Islam di Cordova: (Masa Daulah Bani Umayyah Khalifah ʿAbdu Al-Rahmān Al-Nāṣir) - Maryono Maryono; Riftian Ageng Laksono (STAI Ali bin Abi Thalib Surabaya, 2021)
Cordova is one of the cities that became the center of the development of Islamic knowledge in the West during the reign of the Umayyah Dynasty II in Andalusia (now known as Muslim Spain). During the reign of ʿAbdu Al-Rahmān Al-Nāṣir, Cordova became the most cultured city in Europe, and together with Constantinople and Baghdad, became one of the three cultural centers in the world. This paper aims to describe the intellectual development and knowledge of Islam in Cordova during the Caliph ʿAbdu Al-Rahmān Al-Nāṣir, the Umayyah Dynasty. The method used in this research is descriptive analysis with a historical approach. This method is a process of critically examining and analyzing past records and relics in the form of written text. The results of the literary analysis carried out show that Cordova has made progress in science and culture since it was ruled by the Amirs of Umayyah descent who stood alone apart from the power of the Abbasids in Baghdad. The triumph of Islamic science in Andalusia is very large in Europe, both in science, science, fiqh, language, and literature. The triumph of Islam and intellectual and scientific development to be seen since the Umayyah Dynasty Caliph ʿAbdu Al-Rahmān Al-Nāṣir. Islamic education materials that develop and expand are the Qur'an, theology, Arabic grammar, poetry, lexicography, history, and geography. ʿAbdu Al-Rahmān Al-Nāṣir built a university and developed a library. The University of Cordova stands majestically and becomes an icon of Andalusia so that Andalusia is famous throughout Europe. This university stands upright with the Abdurrahman III Mosque, which in the end developed into a famous higher education equivalent to Al Azhar University in Cairo and Nizamiyah University in Baghdad. Another institution that is the center of scientific civilization and intellectual development is the library. The library is provided for the wider community as a means of learning science. The development of books also increased after the discovery of paper technology in the Islamic world.